Systematic Review: Syndromes, Early Diagnosis, and Treatment in Autoimmune Encephalitis - Hermetter, Christina; Fazekas, Franz; Hochmeister, Sonja (Frontiers in Neurology, 2018)
Over the past few years new antibodies have been discovered to mediate autoimmune encephalitis. This immunological response might be triggered by an infection or a tumour. Classical onconeuronal antibodies are directed against intracellular neuronal agents, but recently a novel group of antibodies to neuronal cell-surface and synaptic antigens associated with different CNS-syndromes has been discovered. Interestingly, in this group the syndromes can be successfully treated with immunotherapy and frequently do not have underlying tumours. The aim of this review is to lay out the current state of knowledge about autoimmune encephalitis in order to provide clinicians a concise up-to-date overview. A comprehensive literature search in medical databases was therefore performed. The literature was carefully studied, new findings focusing on the symptoms, diagnosis and treatment summarized and interpreted. Even though it might be challenging in some cases, the awareness of certain symptom constellations, demographic information in combination with laboratory- and MRI-results allows clinicians to make the diagnosis of probable autoimmune encephalitis at an early stage. Treatment can be initiated faster which improves the outcome remarkably. Further investigations could define underlying pathogenic mechanisms. Randomized controlled trials paired with increasing clinical experience will be necessary to improve the identification of affected patients, treatment strategies and outcomes in the following years.